Phosphate Fractions in Sediments of Aquaculture Systems of Cochin - Ashraf. P., Muhamed; Edwin, Leela; A.G., Gopalakrishna Pillai; K., Ravindran (Fishery Technology, 2025)
This study aims to present quantitative information on various phosphate fractions in the aquaculture farms located in and around Cochin. The results of the analysis of soil samples have shown that loosely bound P was negligible (0.0-0.02 ppm) in all the samples. Concentrations of other fractions viz., Al bound P, Fe bound P, Ca bound P, inorganic P and total P were in the range of 1-68 ppm, 16-159 ppm, 38-428 ppm, 339-633 ppm and 363-705 ppm, respectively. The P concentration in water samples ranged from 0 to 0.325 ppm.